EXPLORING THE CULINARY LANDSCAPE: A LITERATURE REVIEW ON GASTRONOMY AND WINE TOURISM - Zrnić, Miloš (The Business of Tourism, 2024)
With a focus on the dynamic intersections of gastronomy, wine, and gastronomy tourism, a wide range of books, articles, and papers published from 2014 onwards were examined for this literature study. Through the utilization of prestigious academic journals, business magazines, and scholarly books, this research aims to document the most recent advancements, perspectives, and patterns influencing the food scene. The paper makes use of synthesis and analysis techniques. Furthermore, author was able to compare works, research, and studies about wine tourism, gastronomy in general, and gastronomy and wine tourism thanks to the comparative and deductive methods. By casting a wide net over the scholarly landscape, encompassing diverse disciplines such as anthropology, sociology, hospitality management, and tourism studies, this literature review aims to capture the multifaceted dimensions of wine an gastronomy tourism. Through this interdisciplinary approach, this study unravel the complex interplay of cultural, economic, and social factors that shape culinary practices, wine appreciation, and travel experiences around the globe.
Keywords: Gastronomy; wine; gastronomy tourism; wine tourism; tourism